Let's get comprehensive: European Union engagement in fragile and conflict-affected countries - Mark Furness (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The European Union is one of the world's most important actors in assisting fragile and conflict-affected countries, and has made engagement with `fragile states' a top priority for its development policy. At the policy level, the EU's approach is in line with international best practices defined by the OECD's 2007 Principles and the 2011 Busan `New Deal' for fragile states. At the operational level, the EU is developing a `comprehensive approach' to the implementation of its policies. As is the case with most international actors that engage with fragile and conflict-affected countries, a multidimensional gap exists between the intentions expressed at the policy level and the reality of operations at the country level. This paper argues that three sets of factors intervene between the policy and the operations level: cognitive factors related to turning knowledge of partner-country political processes into appropriate actions; issue-related conflicts of interest and trade-offs; and actor-related factors concerning coordination and capacity. This paper discusses how these factors affect the implementation of the EU's policy frameworks with reference to three fragile and conflict-affected countries: South Sudan, Nepal and Liberia.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten